2012
DOI: 10.1098/rsta.2011.0276
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-containing bioactive phosphate glasses

Abstract: The use of biomaterials has revolutionized the biomedical field and has received substantial attention in the last two decades. Among the various types of biomaterials, phosphate glasses have generated great interest on account of their remarkable bioactivity and favourable physical properties for various biomedical applications relating to both hard and soft tissue regeneration. This review paper focuses mainly on the development of titanium-containing phosphate-based glasses and presents an overview of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 114 publications
(177 reference statements)
2
27
0
2
Order By: Relevance
“…The ability to introduce new oxides to the basic sodium-calcium phosphate glass network is of great interest as it allows properties such as their dissolution rates to be tailored (see for example works studying the effect of MgO [10], TiO 2 [11] and Fe 2 O 3 [12]) and the addition of therapeutic ions for controlled release into the body [13].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to introduce new oxides to the basic sodium-calcium phosphate glass network is of great interest as it allows properties such as their dissolution rates to be tailored (see for example works studying the effect of MgO [10], TiO 2 [11] and Fe 2 O 3 [12]) and the addition of therapeutic ions for controlled release into the body [13].…”
Section: Introductionmentioning
confidence: 99%
“…FTIR analysis showed that the infrared spectra of the hybrid fibers after their deposition by electrospinning exhibited the characteristic absorbance peaks of PLA and additional signals related to phosphate complexes ( Figure 5). The PO 4 3-tetrahedron, the basic building block of phosphatebased glasses, 28,42 is present in the fibers, as represented by the absorbance observed at numerous wavelengths. P-O-P stretching modes are also clearly visible on the spectrum.…”
mentioning
confidence: 99%
“…These ORMOGLASSES, however, favor cell attachment, proliferation, and differentiation. 42 It is thus already commonly accepted that such bioactive glasses should rather be used with cells than for an efficient mineralization. 42,57 In fact, Monem et al demonstrated that it is not necessary to require a chemical link between calcium phosphate compounds and the host tissue, because other variables of the material may also promote bone growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has involved both theoretical methods as well as experimental approaches. Here, Kiani et al [73] discuss the range of techniques that have been used to elucidate the structure of phosphate glasses, focusing on the network connectivity information which can be obtained from two-dimensional magic angle spinning (MAS) NMR correlation experiments. They show how this has led to progress in the processing of these glasses, by describing the structural chemistry of titanium dopants in phosphate glasses.…”
Section: Need For a More Rational Approachmentioning
confidence: 99%